A novel Mathematical Modeling for Deep Multilayer Perceptron Optimization: Architecture Optimization and Activation Functions Selection - Taoufyq Elansari; Mohammed Ouanan; Hamid Bourray (Statistics, Optimization & Information Computing, 2024)
The Multilayer Perceptron (MLP) is an artificial neural network composed of one or more hidden layers. It has found wide use in various fields and applications. The number of neurons in the hidden layers, the number of hidden layers, and the activation functions employed in each layer significantly influence the convergence of MLP learning algorithms. This article presents a model for selecting activation functions and optimizing the structure of the multilayer perceptron, formulated in terms of mixed-variable optimization. To solve the obtained model, a hybrid algorithm is used, combining stochastic optimization and the backpropagation algorithm. Our algorithm shows better complexity and execution time compared to some other methods in the literature, as the numerical results show.